Classrooms without Boundaries: Arabic Learning Innovation through Digital Technology - Nikmatul Makfiro; Mohammad Samsul Ulum; Ridwan Ridwan; Muhammed Yahya Kader; Nasiba Kamalova A'zambekovna (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Major changes in education in the digital age have encouraged non-formal institutions to innovate, including the KUBA program in Malang. Limited space, time, and resources have made digital technology a key strategy for expanding access and supporting contextual learning. This study analyzes the use of digital technology in Arabic language learning at KUBA Malang, focusing on teacher strategies, participant engagement, and challenges encountered. A qualitative case study was applied, with data collected through semi-structured interviews and documentation, then analyzed using the Miles, Huberman, and Saldaña model with triangulation of sources. The results show that KUBA integrates Google Meet for online classes, WhatsApp for coordination, and Quizizz for assessment. Innovations are seen in digital comics, animated videos, and native speaker audio, which facilitate vocabulary learning and improve speaking skills. The main challenge is unstable internet connection, which is overcome by providing class recordings for students who cannot attend or experience technical problems. KUBA also offers guidance in routine speaking activities to support material and mental readiness. This study concludes that creative digital media at KUBA Malang not only expands access but also offers an innovative approach that is relevant to non-formal education in the digital era.